A New Add‐On Flap for Performance Improvement of Small Horizontal Axis Wind Turbines - Nima Alizadeh; Alireza Jahangirian (Energy Science & Engineering)
ABSTRACT In the present study, two types of add‐on flaps tangential to the camber line of small horizontal axis wind turbine blade are introduced and their performances on the production power are investigated. The wind turbine of Berlin University (TU‐BERT) is used as the base turbine and the flaps' length, angle, and their locations on the blade are selected as geometric variables. The generated turbine power is calculated numerically by solving three‐dimensional Navier–Stokes equations with a finite volume method using SST k–ω turbulence model. After parametric study considering the effects of flap geometric variables on the production power, a proper arrangement of flaps is proposed. Results show that the straight and curved flaps with the best flap arrangement are able to increase the power coefficient of the wind turbine by 5.8% and 10.5%, respectively, at the rated wind speed of 5.5 m/s and tip speed ratio of 4.5.